2004
DOI: 10.1080/10473289.2004.10470985
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Speciation of PM2.5Collected during Prescribed Fires of the Coconino National Forest near Flagstaff, Arizona

Abstract: The use of prescribed fire is expected to increase in an effort to reduce the risk of catastrophic fire, particularly at urban/forest interfaces. Fire is a well-known source of particulate matter (PM) with particle sizes Յ2.5 m (PM 2.5 ), small diameter PM known to affect climate, visibility, and human health. In this work, PM 2.5 was collected during seven first-entry burns (flaming and smoldering stages) and one maintenance burn of the Coconino National Forest. and sulfate), and 48 elements (with atomic weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
(89 reference statements)
2
18
0
Order By: Relevance
“…In particular, fine and ultrafine PM from ENCF-1 had higher OC content suggesting they were enriched with wildfire smoke, while the PM samples from the ENCF-4 period had higher concentrations of NH 4 + and SO 4 2− indicating that the pollution from this period reflected typical secondary particulate air pollution for the region [37]. The OC mass fractions from ENCF-1 were in good agreement with reported data from the 2005 peat fires in Indonesia [38], while forest fires often produce even higher OC levels (typically > 90% by mass) [35], suggesting that OC levels are affected not only by the different combustion stages but also the type (i.e., fuel source) of wildfires. It should be noted that the wind speed during ENCF-1 was higher than during ENCF-4 and the prevailing wind was from the South-west, while ENCF-4 wind conditions were in general lighter and more southerly in nature with some periods of wind from other directions.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In particular, fine and ultrafine PM from ENCF-1 had higher OC content suggesting they were enriched with wildfire smoke, while the PM samples from the ENCF-4 period had higher concentrations of NH 4 + and SO 4 2− indicating that the pollution from this period reflected typical secondary particulate air pollution for the region [37]. The OC mass fractions from ENCF-1 were in good agreement with reported data from the 2005 peat fires in Indonesia [38], while forest fires often produce even higher OC levels (typically > 90% by mass) [35], suggesting that OC levels are affected not only by the different combustion stages but also the type (i.e., fuel source) of wildfires. It should be noted that the wind speed during ENCF-1 was higher than during ENCF-4 and the prevailing wind was from the South-west, while ENCF-4 wind conditions were in general lighter and more southerly in nature with some periods of wind from other directions.…”
Section: Discussionsupporting
confidence: 61%
“…Compared to emissions from different wildfire types (e.g., savanna, forest, and woodland fires), peat fires produce >100% more CO and >300% more CH 4 , suggesting that they may have a greater impact on human health and climate change [34]. Robinson et al [35] reported that flaming and smoldering combustion stages of wildfire produced distinctly different ionic and elemental compositions of fine PM, but other size fractions were not assessed. Here we found that the coarse PM from both sampling periods had similar elemental composition, while the fine and ultrafine PM (which form through nucleation, condensation, and coagulation processes) differed between the smoldering and the glowing phases of the burn [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smouldering burning conditions are more dominant in boreal forest fires and peat fires than in grass, shrub or cereal waste fires, which mainly burn in flaming conditions Lavoue et al, 2000;Ortiz de Zárate et al, 2000;Soja et al, 2004). Thus, it seems likely that aerosols from forest and peat fires were less enriched with K than aerosols from agricultural field burning since the fraction of K is lower in the emissions from smouldering fires than in those from flaming fires Gaudichet et al, 1995;Robinson et al, 2004). Another reason for the relatively low proportion of K was probably the mixing of emissions from fossil fuel burning since air masses arrived from the regions of Eastern Europe with high S emissions (EMEP, 2001).…”
Section: Sem/edx Analysesmentioning
confidence: 99%
“…Biomass burning and wildfires emit a vast quantity of soot and OC-bearing smoke [25]. Smoke exposures have been known to exacerbate allergic asthma and increase the severity of cardiovascular disease.…”
Section: Effects Of Organic Compounds In Wildfire Pm On Lung Inflammamentioning
confidence: 99%